2020
DOI: 10.3389/fevo.2020.00131
|View full text |Cite
|
Sign up to set email alerts
|

Streetlights Disrupt Night-Time Sleep in Urban Black Swans

Abstract: Artificial light at night could have widespread and detrimental impacts on sleep. To reduce disruptive effects of artificial light on sleep in humans, most smartphones and computers now have software that reduces blue light emissions at night. Little is known about whether reducing blue light emissions from city lights could also benefit urban wildlife. We investigated the effects of blue-rich (white) and blue-reduced (amber) LED streetlights on accelerometry-defined rest, electrophysiologically-identified sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 69 publications
1
9
0
1
Order By: Relevance
“…Studies of sensory function during sleep in wildlife are sparse; however, new studies are suggestive of impacts from both noise and light given the important role of hearing as a crucial alerting function during sleep and because light exposure appears to influence multiple physiological systems. Light disrupts the intensity, continuity and length of sleep in birds (Aulsebrook et al 2020a,b) and noise appears to fragment and degrade sleep in birds much as it does in humans (Connelly et al 2020). Thus, additional work is necessary to understand whether the costs of noise and light exposure are greater for nocturnal or diurnal species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of sensory function during sleep in wildlife are sparse; however, new studies are suggestive of impacts from both noise and light given the important role of hearing as a crucial alerting function during sleep and because light exposure appears to influence multiple physiological systems. Light disrupts the intensity, continuity and length of sleep in birds (Aulsebrook et al 2020a,b) and noise appears to fragment and degrade sleep in birds much as it does in humans (Connelly et al 2020). Thus, additional work is necessary to understand whether the costs of noise and light exposure are greater for nocturnal or diurnal species.…”
Section: Discussionmentioning
confidence: 99%
“…Some birds, such as great tits ( Parus major ), are too small to bear the weight of even the smallest EEG data loggers [ 43 ]. Others, such as water birds, live in environments where successfully deploying and retrieving data loggers is challenging [ 44 ]. Although advances in technology are gradually overcoming these issues, existing studies have often relied exclusively on behavior to characterize avian sleep.…”
Section: Characterizing Avian Sleepmentioning
confidence: 99%
“…The findings for geese were partially supported by a subsequent study [ 63 ], which found decreased non-REM sleep during a full moon in winter, but not in summer. In another study conducted during summer, Aulsebrook et al [ 44 ] also found no effect of the lunar phase on the total amount of sleep in black swans ( Cygnus atratus ). This latter study on swans used activity as a proxy for sleep (non-REM and REM sleep combined) after validation with recordings of the EEG, such that it was not possible to distinguish between non-REM and REM sleep.…”
Section: Light Regulates and Suppresses Sleep In Diurnal Birdsmentioning
confidence: 99%
See 2 more Smart Citations